Oxygen‐Promoted CH Bond Activation at Palladium. Issue 25 (9th May 2014) - Scheuermann, Margaret L.; Boyce, David W.; Grice, Kyle A.; Kaminsky, Werner; Stoll, Stefan; Tolman, William B.; Swang, Ole; Goldberg, Karen I.
Abstract: [Pd(P(Ar)( t Bu)2 )2 ] (1, Ar=naphthyl) reacts with molecular oxygen to form Pd II hydroxide dimers in which the naphthyl ring is cyclometalated and one equivalent of phosphine per palladium atom is released. This reaction involves the cleavage of both CH and OO bonds, two transformations central to catalytic aerobic oxidizations of hydrocarbons. Observations at low temperature suggest the initial formation of a superoxo complex, which then generates a peroxo complex prior to the CH activation step. A transition state for energetically viable CH activation across a Pdperoxo bond was located computationally. Abstract : Oxygen leads the way : [Pd(P(Ar)( t Bu)2 )2 ] (Ar=naphthyl) undergoes a reaction with molecular oxygen in which CH and OO bonds are cleaved. Observation of the reaction at low temperature suggests the initial formation of a superoxo complex, which then generates a peroxo complex prior to the CH activation step. The transition state for an energetically viable CH activation across a Pdperoxo bond was located computationally.